Intrusions of South Atlantic Central Water on the Espírito Santo Basin shelf (18ºS-22ºS, Brazil) - Palóczy Filho, André (2015)
The intrusion pathways and physical mechanisms associated with intrusions of cold, nutrient-rich South Atlantic Central Water (SACW) onto the continental shelf of the Espírito Santo Basin (ESB), off southeast Brazil (18°S-22°S), are investigated. The approach consists of analyses of a set of simplified, process-oriented, primitive-equation numerical models supported by the analyses of an independent, more realistic numerical model and available observations. The cross-isobath circulation is found to be strongly dominated by wind-driving, consistent with previous findings. In the model experiments, SACW enters the ESB shelf through two preferential pathways along the Tubarão Bight area (TB, 19.5°S-22°S). These pathways are found to be locations where an equatorward along-isobath pressure gradient force (PGFy∗) of ∼2 x 10-6 m s-2 develops in response to steady wind forcing. This equatorward PGFy∗ is essentially in geostrophic balance, and therefore induces onshore flow across the shelf edge and most of the shelf proper. The Brazil Current (BC) imparts an additional equatorward PGFy∗ on the shelf. The momentum budget reveals that the ageostrophic residue of the PGFy∗ is compensated mostly by momentum advection and bottom friction. Buoyancy arrest might be important under more intense SACW intrusion events, as suggested by the maximum observed values of the slope Burger number (0.32-0.92). Among the deep ocean forcing mechanisms considered, the intrinsic pycnocline uplifting effect of the BC seems to be responsible for ∼1.4°C colder upwelled water under steady, upwelling-favorable wind forcing, relative to a flat stratification scenario. The BC also seems to induce local intrusions by inertially overshooting the shelf edge, consistent with Rossby numbers of ∼0.3-0.5, as estimated for the area along the TB shelf edge. Finally, the planetary β-effect is also related to a background equatorward PGFy∗. In addition, the steady response of the continental shelf to a periodic (in the along-shelf direction) pressure forcing at the shelf edge is compared with the BC-forced primitive-equation numerical solutions. A simple Arrested Topographic Wave (ATW) analytical model is found to be successful in representing the general features of the numerical solutions. The cross-shelf e-folding scales of the cross-shelf velocity estimated from the numerical solutions agree in order of magnitude with the cross-shelf penetration scale q-1 = [-2r/(lfs)]½ = 10 km predicted by the ATW, where r is a linear bottom resistance parameter, l is the along-shelf wavenumber of the forcing at the shelf edge, f is the Coriolis parameter and s is the bottom slope. Furthermore, the use of quadratic bottom stress accounts for some of the relative increase in the numerical onshore penetration scales, which are predicted to be qquadratic-1 = [-2CD/(lfs)]½ [Ubot]½, where CD is a quadratic bottom friction parameter and Ubot is the near-bottom velocity magnitude. The kind of steady response to periodic deep ocean forcing examined here may provide insight into other continental shelves under the influence of western boundary currents.